Advance energy storage system for green building application - Ong, Cherie Hui Ling. (2013)
Back in the early days, the need to send power over long distances to rural and surburban area was utmost priority. Unlike the Direct Current (DC), alternating current (AC) is able to transmit over a long distances in a relatively reasonable cable size. In addition, the high output voltage from the main source can be easily transform into a desired voltage level before it is feed to the residential and commercial power system. In addition, back than many of the household devices requires AC power to operate which makes it more logical to integrate the AC power system.